-2a(a+3)=

Simple and best practice solution for -2a(a+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a(a+3)= equation:


Simplifying
-2a(a + 3) = 0

Reorder the terms:
-2a(3 + a) = 0
(3 * -2a + a * -2a) = 0
(-6a + -2a2) = 0

Solving
-6a + -2a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '-2a'.
-2a(3 + a) = 0

Ignore the factor -2.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(3 + a)' equal to zero and attempt to solve: Simplifying 3 + a = 0 Solving 3 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + a = 0 + -3 a = 0 + -3 Combine like terms: 0 + -3 = -3 a = -3 Simplifying a = -3

Solution

a = {0, -3}

See similar equations:

| 3x-12x+1=6x+3-15+4 | | (2x^3)(-4x^6)(3x^2)= | | x-12x+1=2x+1-15x+4 | | Y+6x=6 | | 3x+78=67 | | 2x+4=3x+0 | | 14-4x=-2x-6 | | 22/7= | | 10w/4w^2 | | 3(5)+5x=-15 | | 1018.395/16.5+5= | | (x-3)(x-3)=10 | | 0=16t^2+32t | | 3y+5(-3)=-15 | | G(2)=3t-7 | | 8(2+2)=4(2+1)-20 | | 9t+14-5t-7=29 | | m^2-30=7m | | 10x^2-12x-9=0 | | w/x=y/z | | 0.5x-3(40+x)=0.3(40) | | y+2(2)=1 | | 9/10x=27 | | y+2(-3)=1 | | -8+6x=34x+24 | | F^2-3r=28 | | 1/2m2+1/4n2 | | 2p-1/9 | | 144=-13(x+5) | | 0=6-6x | | 4x^4+36x^2=0 | | 9x-3=-2x-18 |

Equations solver categories